2003
DOI: 10.1016/s0038-1098(03)00144-3
|View full text |Cite
|
Sign up to set email alerts
|

Martensitic transition and structural modulations in the Heusler alloy Ni2FeGa

Abstract: We have found two distinctive structural modulations altering evidently along with the martensitic transition (MT) in the Ni 2 FeGa alloy. The first one ðq 1 Þ; corresponding to the well-known phonon anomalies in the ½zz0 TA 2 branch, occurs along the k110l direction. The second one ðq 2 Þ; an incommensurate modulation observed for the first time, occurs along the k211l-direction. Both modulations change gradually with the premartensitic phonon softening and discontinuously with the MT. Anomalies in magnetic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 13 publications
5
16
0
Order By: Relevance
“…It is worthy to note that two sets of satellite reflections are visible around each fundamental Bragg spot. They are considered to be caused by the structural modulation, which was also reported in the Ni 2 FeGa alloys [22,23]. However, the modulated structure was not detected by XRD measurement.…”
Section: Martensitic Transformation Behaviorsmentioning
confidence: 84%
“…It is worthy to note that two sets of satellite reflections are visible around each fundamental Bragg spot. They are considered to be caused by the structural modulation, which was also reported in the Ni 2 FeGa alloys [22,23]. However, the modulated structure was not detected by XRD measurement.…”
Section: Martensitic Transformation Behaviorsmentioning
confidence: 84%
“…and magnetic-field-induced strain, etc., have been extensively discussed [11][12][13][14][15][16][17]. It is also noted that numerous types of superstructure modulations appear along with martensitic transition at low temperatures [18,19]. For Ni 2 FeGa, it is found that, with increasing Ni concentration in ribbons, the martensitic transformation temperature increases progressively, on the other hand, the Curie temperature decreases from 440 to 312 K [3].…”
Section: Introductionmentioning
confidence: 98%
“…Recently new promising FSMAs have been found in Fe-Ni-Ga alloys [10][11][12][13]. These alloys are characterized by a wide range of T M from ∼150 to ∼300 K and excellent ductility.…”
Section: Introductionmentioning
confidence: 99%